2022
DOI: 10.1007/s11033-022-08184-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre exposure to enriched environment alleviates brain injury after ischemia-reperfusion by inhibiting p38MAPK/STAT1 pathway

Abstract: Background Stroke is one of the major diseases that endangers human health. It is widely reported that enriched environment (EE) can improve the neurological function in different brain injury models. Recently, relevant researches have indicated that MAPK pathway is closely related to the inflammatory response in nervous system related diseases. However, whether pre exposure to EE (EE pretreatment) has a preventive effect, and its mechanism are not clear. Therefore, this study aimed to determine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Recently, the MAPK pathway has been confirmed to be closely related to the inflammatory response in nervous system diseases. Studies have confirmed that EE preconditioning can have a protective effect on acute ischemic stroke by inhibiting p38 MAPK/STAT1 pathway [ 45 ]. In addition, EE promotes functional recovery after stroke by inhibiting calpain 1 activity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the MAPK pathway has been confirmed to be closely related to the inflammatory response in nervous system diseases. Studies have confirmed that EE preconditioning can have a protective effect on acute ischemic stroke by inhibiting p38 MAPK/STAT1 pathway [ 45 ]. In addition, EE promotes functional recovery after stroke by inhibiting calpain 1 activity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%